Arthonia dokdoensis and Rufoplaca toktoana – Two New Taxa from Dokdo Islands (South Korea). Issue 4 (2nd October 2019) - Kondratyuk, Sergij; Lőkös, László; Halda, Josef; Lee, Beeyoung Gun; Jang, Seol-Hwa; Woo, Jeong-Jae; Park, Jung Shin; Oh, Soon-Ok; Han, Sang-Kuk; Hur, Jae-Seoun
Abstract: Arthonia dokdoensis sp. nov., a lichenicolous fungus from the subcosmopolitan Arthonia molendoi complex growing on crustose thalli of species of the genus Orientophila (subfamily Xanthorioideae, Teloschistaceae), as well as the lichen species Rufoplaca toktoana sp. nov. (subfamily Caloplacoideae, Teloschistaceae) similar to Rufoplaca kaernefeltiana, both from Dokdo Islands, Republic of Korea, are described, illustrated, and compared with closely related taxa. In the phylogenetic tree of the Arthoniaceae based on 12S mtSSU and RPB2 gene sequences, the phylogenetic position of the A. dokdoensis and the relationship with the A. molendoi group are illustrated, while the position of the newly described R. toktoana is confirmed by phylogenetic tree based on ITS nrDNA data.